Menghitung Debit Air Limpasan di PT. Kalimantan Prima Persada Jobsite PELH Desa Kebur, Kecamatan Merapi Barat, Kabupaten Lahat, Provinsi Sumatera Selatan - Rijalnur Hidayatullah; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2023)
PT. Kalimantan Prima Persada Jobsite PELH is mining company operating in the field of coal mining contractors. Mining system carried out by PT. Kalimantan Prima Persada Jobsite PELH use the open pit mining method, during rainy season, problem that is often found is water. Water that comes from above the ground surface (runoff water) and water that is below the ground surface (ground water). Runoff water and ground water are the main things that must be considered so that they do not disturb and damage the mining location. Therefore, this report was written to find out how much runoff water enters the mining front area. The stages used in calculating runoff water discharge are calculating the catchment area area, calculating planned rainfall data using the Log Pearson III method, calculating rain intensity using the Monnonobe method, calculating runoff water discharge using the rational method. Based on calculations, the catchment area in Pit PE PT was obtained. Kalimantan Prima Persada Jobsite PELH is 13,821 Ha or 0.13821 km2, the average daily maximum rainfall in the last 10 years is 547.4 mm/day, arranged rainfalll is 696.13 mm/day, intensity of rain is 398.66 mm/day, and the runoff discharge is 49,626 m3/hour.